Circular Economy 4 Colombia innovation challenge 2025: Accelerator Program and Demo Day Report - Khader, Taija; Sanchez Miller, Hannah (2025)
The Alliance of Bioversity International and CIAT's Research Initiative on Nature-Positive Solutions launched its CircularEconomy4Colombia (CE4C) Innovation Challenge. The CE4C initiative is powered by the CGIAR Accelerate for Impact Platform (A4IP), and aims to accelerate Colombia’s transition by fostering technological and scientific solutions in the agri-food sector. Its objectives include identifying high-potential startups, providing tailored acceleration, strengthening networks among innovators, investors, and policymakers, and promoting knowledge exchange to reinforce the country’s circular economy ecosystem. Read our Accelerator and Demo Day Report.